(untitled) (MAUSAM, 1970)
Persistence of both the 12-month,and 6-month oscillations in the annual variation of amplitudes of the first two harmonics monthly mean Sq (H) for Alibag and of a large change during the later half of the year in the phase angles are observed during different solar cycles. The same features are found for a few other stations. The semi-annual components variation in amplitudes is found to be the predominant feature for stations close to the geomagnetic equator. Possible causes of the features observed are discussed.